1985
DOI: 10.1073/pnas.82.21.7364
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease: isolation of a cDNA clone encoding human alpha-galactosidase A.

Abstract: Fabry disease is an X-linked inborn error of metabolism resulting from the deficient activity of the lysosomal hydrolase, a-galactosidase A (a-Gal A; a-Dgalactoside galactohydrolase, EC 3.2.1.22). To investigate the structure, organization, and expression of a-Gal A, as well as the nature of mutations in Fabry disease, a clone encoding human a-Gal A was isolated from a Agtll human liver cDNA expression library. To facilitate screening, an improved affinity purification procedure was used to obtain sufficient h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…Lanes 4^6 are three lots of enzyme ¢nished with separate chromatography conditions. The highest speci¢c enzyme activity reported previously for Gal-A was 5.0 Â 10 6 units mg 71 (Calhoun et al 1985) for enzyme isolated from human lung tissue. Gal-A puri¢ed from transfected leaves routinely has a speci¢c activity of over 5.5 Â 10 6 units mg À1 protein.…”
Section: Tmv Biotechnology T H Turpen 669mentioning
confidence: 88%
“…Lanes 4^6 are three lots of enzyme ¢nished with separate chromatography conditions. The highest speci¢c enzyme activity reported previously for Gal-A was 5.0 Â 10 6 units mg 71 (Calhoun et al 1985) for enzyme isolated from human lung tissue. Gal-A puri¢ed from transfected leaves routinely has a speci¢c activity of over 5.5 Â 10 6 units mg À1 protein.…”
Section: Tmv Biotechnology T H Turpen 669mentioning
confidence: 88%
“…Since cDNA of a-GalA was cloned and characterized (Calhoun et aL, 1985;Bishop et aL, 1986), molecular abnormalities in more than one hundred families with Fabry disease have been studied. Bernstein et al (1989) reported that partial gene deletions were seen only seven families out of 130 families by Southern blotting analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the full-length cDNA encoding human a-GalA has been isolated and characterized (Calhoun et al, 1985;Bishop et al, 1986Bishop et al, , 1988Kornreich et al, 1989). Since then molecular analysis of this disease has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the cloning and nucleotide sequence of a cDNA (AAG18) encoding the entire mature lysosomal form of human a-Gal A (15,16). The AAG18 cDNA did not contain the entire 5' sequence and encoded only five residues of the a-Gal A signal peptide.…”
mentioning
confidence: 99%